Validity of Rating of Perceived Exertion (RPE) on Training Intensity in Recreational Runner - Bagus Tri Budi Antoro; Apriantono, Tommy; Ferryanto, Ferryanto (Universitas PGRI Palembang, 2024)
The purpose of this research is to determine whether or not the Rating of Perceived Exertion (RPE) is a reliable instrument for determining the level of vigour with which recreational runners engage in their workouts. Information was gathered from a number of runners who were engaged in training of varied intensities, and their RPE ratings were compared with other techniques of determining the intensity of their training. According to the findings of the investigation, there is a significant association between the RPE scores and the actual severity of the training, which suggests that RPE has the potential to be a useful tool in assisting runners in regulating the intensity of their training. On the other hand, this research has certain shortcomings, such as the use of subjective measuring techniques, a very small sample size, and the possibility of bias in the RPE response. An improvement in the validity and accuracy of the use of RPE, an investigation into the variables that impact perceptions of exercise intensity, and an evaluation of the association between RPE and long-term exercise results are some of the recommendations for future study.